Circulation Pathways and Exports of Arctic River Runoff Influenced by Atmospheric Circulation Regimes - Wang, Qiang; Danilov, Sergey; Sidorenko, Dmitry; Wang, Xuezhu (Frontiers in Marine Science, 2021)
River runoff supplies the Arctic Ocean with a large amount of freshwater and land-derived material, so it is important for both the physical and biogeochemical marine environment. In this study, we used wind perturbation simulations to elucidate the response of the circulation pathways and exports of Arctic river runoff to different atmospheric circulation regimes. Specifically, wind perturbations representing the negative and positive phases of the Arctic Oscillation and Beaufort High modes were imposed over the Arctic Ocean separately in different sensitivity experiments. In addition, some combinations of the two modes were also considered in sensitivity experiments. By comparing these experiments with a control simulation, we revealed the impact of different wind perturbations. The atmospheric circulation regimes influence the Arctic surface geostrophic currents through changing the halosteric height, which is associated with the changes in spatial distribution of surface freshwater. The circulation pathways of river runoff, and Pacific and Atlantic derived surface waters are mainly determined by the surface geostrophic currents. The positive (negative) Arctic Oscillation reduces (increases) freshwater storage and sea surface height in the Makarov and Eurasian basins, thus strengthening (weakening) the cyclonic circulation and weakening (strengthening) the anticyclonic circulation; Accordingly, the Eurasian runoff leaves the Siberian shelf at more eastern (western) locations, and has an enhanced export through the Fram Strait (Canadian Arctic Archipelago). The positive (negative) Beaufort High increases (reduces) freshwater storage and sea surface height in the Amerasian Basin, thus strengthening (weakening) the anticyclonic circulation; Accordingly, the Eurasian runoff export through the Fram Strait and the Mackenzier River runoff export through the Canadian Arctic Archipelago are reduced (increased). The positive Arctic Oscillation increases freshwater available to the Beaufort Gyre, which can be efficiently accumulated there in the presence of a positive Beaufort High forcing. The impact of the Beaufort High mode on the location of the Transpolar Drift Stream and runoff circulation pathways is stronger with a positive Arctic Oscillation than with a neutral Arctic Oscillation state. Our results also showed that Eurasian runoff can only have a relatively small contribution to freshwater accumulation in the Beaufort Gyre region.